A Study of Trend of Price/Net Operating Revenue and Earnings Yield of Selected Public Sector Companies in India - et. al., Dr. Jyoti Prasad Kalita, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study's aim is to uncover the Trend of Price/Net Operating Revenue and Earnings Yield of Selected Public Sector Companies in India. The analysis of variance is used in the analysis to determine the trend difference in Price/Net Operating Revenue and Earnings Yield of public sector companies. The research takes into account a variety of financial ratios from firms in the Maharatna and Navrtana categories. Study’s findings are extremely helpful to investors in determining the financial strength of PSUs. It has a huge effect on public-sector expenditure decisions.